Determinants of Earnings Quality (Case Study of Mining Sector Manufacturing Companies on the Indonesian Stock Exchange 2021-2022) - Febriana, Michelle; Aminah, Aminah; Afrizal, Afrizal (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Earnings quality is one of the many factors used by investors as a basis for making investment activity decisions. Good quality company profits are profits that can reflect the company's real or actual financial condition. Several financial ratios can influence the high or low quality of a company's profits. This research aims to test whether liquidity, leverage and institutional ownership structure have an influence on the profit quality of mining sector manufacturing companies listed on the IDX in 2021-2022. The population and sample for this study were selected based on purposive sampling of 28 companies. The data collected is secondary data using documentation techniques. The data analysis technique used is multiple linear regression analysis. The results of this research state that liquidity, leverage, and ownership structure partially or simultaneously have a positive and significant influence on the quality of company profits.